Closed traumatic rupture of both flexor tendons in a child - (:unkn) unknown (My University, 2011)
Closed traumatic rupture of both flexors in hand fingers without underlying disease is uncommon and are often missed on initial presentation. Especially in children the diagnosis is more complicated. A four years old girl presented with flexion inability of fourth finger of her left hand without any scar. With a careful investigation on the history and phsical examination, there weren't any suspecious clue for any other previous laceration. During examination, the patient was not able to flex actively any of the interphalangial joints. Patient go to the surgery and the rupture of both flexors tendon also seen during surgery which has not been reported before in the literature. Profundus tendon was repaired by using superficalis tendon as a tendon graft. The purpose of this report is to attract attention to early recognition and treatment of closed traumatic rupture of flexor tendons in children.
Keywords: Child; Rupture; Tendons